Produção e valor nutricional de cultivares de azevém consorciados ou não com aveia preta submetidos a dois resíduos de pastejo - Marchesan, Renato (2014)
Ryegrass is one of the most widely used forage species in southern Brazil during the winter, supplying the lack of summer pastures. The aim of this study was to evaluate forage production and nutricional value of ryegrass (Lolium multiflorum Lam) cv. Barjumbo and common ryegrass (Lolium multiflorum) intercropping or not with oats (Avena strigosa Schreb) cv. IAPAR 61 underwent two grazing residues. In addition to defining the ideal time input grazing systems studied. The study was conducted at the Universidade Tecnológica Federal do Paraná, Câmpus Dois Vizinhos, in the period April to September 2012. The experimental design was a 4x2 factorial, totaling eight treatments with three replicates, being evaluated common and barjumbo ryegrass single and intercropped with oat barjumbo in two heights of post-grazing residue: High: 50% of the height of entry; Low: 30% of the height of entry. The results indicated that ryegrass common single and intercropped increased the production and cultivate barjumbo higher accumulation rate comparing both syndicated. But leaf production did not differ among cultivars, only the production of stem which was lower for cultivate barjumbo. Thus the production of oats excluding ryegrass cultivars was higher when it was intercropped with cultivate barjumbo. The point of entry for ryegrass cultivars was 26.86 cm and 28.75 cm for barjumbo to common and when intercropped with oats was 34.01 cm and 32.48 cm respectively. The single barjumbo showed higher crude protein. The levels of neutral detergent fiber and acid detergent fiber were lower for single cultivar and intercropped barjumbo relative to cultivate common and consequently digestibility and total digestible nutrients were higher.